2020
DOI: 10.1002/dac.4590
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage and individuals' intentions toward adopting Bitcoin: The role of the theory of planned behavior and perceived risk

Abstract: Summary Despite the increasing popularity and recognition of cryptocurrencies, little is known about the contextual and psychological variables that predict the behavioral intentions of individuals toward adopting a cryptocurrency such as Bitcoin. Utilizing the extended theory of planned behavior (TPB), authors have developed and tested a theoretical model to investigate the relationship between the usage of social media and the intentions of individuals toward adopting Bitcoin. We empirically tested our conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 68 publications
(123 reference statements)
1
40
0
2
Order By: Relevance
“…The tradition of social media in all walks of life has been increased rapidly in the recent years (Anser et al 2020;Rauniar et al 2014). Past researches revealed that social media is getting popular among students, and recent researchers have noted the considerable influence of social media utilisation in academia (Friesen and Lowe 2012;Greenhow and Lewin 2016;Malik et al 2020).…”
Section: Student Use Of Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…The tradition of social media in all walks of life has been increased rapidly in the recent years (Anser et al 2020;Rauniar et al 2014). Past researches revealed that social media is getting popular among students, and recent researchers have noted the considerable influence of social media utilisation in academia (Friesen and Lowe 2012;Greenhow and Lewin 2016;Malik et al 2020).…”
Section: Student Use Of Social Mediamentioning
confidence: 99%
“…In the recent era, the utilisation of social media platforms in human life has increased rapidly (Anser et al 2020;Sugimoto et al 2017). Social media is being used for a variety of purposes, including messaging, emailing, knowledge sharing, chatting, advertising, buying and selling, booking of airlines and hotels, and studying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such task-related information challenges stressed employees to obtain important information and manage their tasks efficiently. ESM usage could benefit challenge-stressed individuals to gain insight into the possible advantages of tasks, such as promotion or self-development (Cai et al, 2018;Anser et al, 2020;Wang et al, 2021). In addition, ESM usage promotes a strong perception of stressful demands to challenge-stressed individuals, thereby enhancing their willingness to spend their time and energy resolving taskrelated issues (Ding et al, 2019;Nadeem et al, 2020).…”
Section: Socio-instrumental Use Of Esm Work Stressorsmentioning
confidence: 99%
“…With relevant work expertise, individuals can better use the IT applications, including ESM and knowledge management software, and will provide accurate, timely, and useful business information (Lee et al, 2011; Leonardi, 2014; Rashid et al, 2020) that benefit perceived task structure. Past theoretical work has proposed that individual work expertise is essential in enhancing task autonomy and interdependence that needs freedom, control related to the task, and, conversely, timely, relevant information for communication (Anser et al, 2020; Augusto Felício et al, 2014; Salviano et al, 2012). Scholars argue that people who have expertise in work may offer valuable information and will present appropriate knowledge associated with their own experience (Choi, 2016).…”
Section: Introductionmentioning
confidence: 99%